Nondestructive Testing of Pavements and Backcalculation of Moduli: Third Volume 2000
DOI: 10.1520/stp14769s
|View full text |Cite
|
Sign up to set email alerts
|

Use of Instrumented Dynamic Cone Penetrometer in Pavement Characterization

Abstract: The dynamic cone penetrometer data had been conventionally used for estimating the base and subgrade California bearing ratio. In recent years, a need for developing mechanistic pavement design procedures has been emphasized. However to develop mechanistic pavement design procedures, measuring engineering properties of pavement layers is essential. Two modifications to the existing dynamic cone penetrometer have been proposed in this paper for obtaining engineering properties of pavement layers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Using the energy transferred at the cone tip may improve the reliability of the estimation and characterization of cone resistance along the penetration depth. Previous studies suggested various types of dynamic cone resistances based on the transferred energy [ 17 , 19 , 24 ]. Considering that the force squared integration method ( F 2 method) and force–velocity integration method ( F – V method) are widely used for evaluating the transferred energy at the rod head, three different types of dynamic resistances can be calculated as follows: where c and E denote the wave velocity through the steel rod and Young’s modulus of the rod, respectively.…”
Section: Experimental Studymentioning
confidence: 99%
“…Using the energy transferred at the cone tip may improve the reliability of the estimation and characterization of cone resistance along the penetration depth. Previous studies suggested various types of dynamic cone resistances based on the transferred energy [ 17 , 19 , 24 ]. Considering that the force squared integration method ( F 2 method) and force–velocity integration method ( F – V method) are widely used for evaluating the transferred energy at the rod head, three different types of dynamic resistances can be calculated as follows: where c and E denote the wave velocity through the steel rod and Young’s modulus of the rod, respectively.…”
Section: Experimental Studymentioning
confidence: 99%
“…There has been some work done on extracting the actual mechanical properties of soil with a DCP. Nazarian et al (1999) developed two experimental versions of the DCP, for transportation civil engineering, that were tested in pavement bases and subgrains. A "Seismic DCP" (SDCP) was outfitted with a 3-axis accelerometer in the cone tip.…”
Section: Slow Dynamic Penetrometersmentioning
confidence: 99%
“…The second variation created by Nazarian et al (1999) the "Instrumented DCP," was outfitted with a high speed load cell and a single axis accelerometer at the top of the penetrometer rod (where the drop hammer impacts it). The accelerometer was used to determine the time versus velocity and depth data (by single and double integration respectively) and the load cell measured the dynamic force.…”
Section: Slow Dynamic Penetrometersmentioning
confidence: 99%
“…Initially, Langton (1999) introduced a lightweight DCP to measure cone resistance using the energy transferred at the anvil, a technique further refined in subsequent studies (Athapaththu et al, 2007;Tsuchida et al, 2011). In addition, Nazarian et al (2000) developed a DCP equipped with a load cell and an accelerometer on its anvil. Expanding upon these advancements, Byun and Lee (2013) developed an instrumented DCP (IDCP), which measures the energy transmitted at the anvil and cone tip.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nazarian et al. (2000) developed a DCP equipped with a load cell and an accelerometer on its anvil. Expanding upon these advancements, Byun and Lee (2013) developed an instrumented DCP (IDCP), which measures the energy transmitted at the anvil and cone tip.…”
Section: Introductionmentioning
confidence: 99%